CRIMINAL ASPECTS OF HUMAN EMBRYO DONATION UNDER SURROGACY ARRANGEMENTS - Gądzik, Zuzanna Barbara (Zeszyty Prawnicze, 2019)
This article is on criminal liability under Polish law for behaviour related to the donation of embryos that may take place as part of surrogate arrangements. I analyse the features of prohibited acts specified in the provisions of Ustawa z 25 czerwca 2015 r. o leczeniu niepłodności (the Treatment of Infertility Act of 25th June 2015, Dziennik Ustaw 2017, Item 865, uniform text) i.e. embryo disposal or acquisition to derive material or personal benefit, dissemination of advertisements for embryo provision or receipt in return for payment, and embryo handling in breach of the legal provisions. I also refer to descriptions of surrogate maternity and its status in Polish law.